TIPIKAL EVALUASI EKONOMI UNTUK PENINGKATAN STATUS JALAN - Natalia Tanan; Sofyan M. Saleh; Muhammad Isya; Bakauddin Bakauddin (Jurnal Jalan-Jembatan, 2010)
Road as a part of national transportation system has an important role in the economic growth of a region. Therefore, road transportation must arranged to manifest service reliability and integrity with other transportation mode. To produce transportation network taht can give efficiently geography scale of transportation service from global to local, conversely. In this paper, conducted economy evaluation of road status upgrading. The links that be evaluated: the road of kabupaten/kota in Province Aceh, which is in general the condition of the roads are intermediate and poor. Most of the surface are gravel and soil. With the condition, much area potencies not developed yet. From the analysis, obtaned that in Province Aceh must conducted roads status upgrading. The road that will be upgraded become National road are : 3 link which is located in Kota Banda Aceh and Kabupaten Aceh Besar, and the road that will be upgraded become Province road are 66 links that spread in other Kota/Kabupaten unless Simeulue and Sabang. To analyze the economic benefit of the road status upgrading, be used "with and without Project" approach. With existence of this uprading, expected will give benefit for region development and society economy, both direct and inderect benefit. The result of economy evaluation show that upgrading of road status in Province Aceh give value : Nett Present Values = Rp. 797.063.226.209,-, Benefit Cost Ratio = 1,11 ; and Economic Internal Rate of Return = 13,71 % Keyword : region development, road network, road status, economic evaluation, road upgrading